Early impact of moderate preterm birth on the structure, function and gene expression of conduit arteries. Issue 8 (12th June 2020) - Lombardo, Paul; Nguyen, Vivian B.; Flores, Tracey J.; Sutherland, Megan R.; Nitsos, Ilias; Allison, Beth J.; Parkington, Helena; Tare, Marianne; Harding, Richard; De Matteo, Robert; Schneider, Michal; Polglase, Graeme R.; et al.
Abstract : New Findings: What is the central question of this study? What is the immediate impact of moderate preterm birth on the structure and function of major conduit arteries using a pre‐clinical sheep model? What is the main finding and its importance? Postnatal changes in conduit arteries, including a significant decrease in collagen within the thoracic aortic wall (predominately males), narrowed carotid arteries, reduced aortic systolic blood flow, and upregulation of the mRNA expression of cell adhesion and inflammatory markers at 2 days of age in preterm lambs compared to controls, may increase the risk of cardiovascular impairment in later life. Abstract: The aim of this work was to compare the structure and function of the conduit arteries of moderately preterm and term‐born lambs and to determine whether vascular injury‐associated genes were upregulated. Time‐mated ewes were induced to deliver either preterm (132 ± 1 days of gestation; n  = 11 females and n  = 10 males) or at term (147 ± 1 days of gestation; n  = 10 females and n  = 5 males). Two days after birth, ultrasound imaging of the proximal ascending aorta, main, right and left pulmonary arteries, and right and left common carotid arteries was conducted in anaesthetized lambs. Lambs were then killed and segments of the thoracic aorta and left common carotid artery were either snap frozen for real‐time PCR analyses or immersion‐fixed for histological quantification of collagen, smooth muscle and elastin within the medial layer. Overall there were few differences in vascular structure between moderately preterm and term lambs. However, there was a significant decrease in the proportion of collagen within the thoracic aortic wall (predominantly in males), narrowing of the common carotid arteries and a reduction in peak aortic systolic blood flow in preterm lambs. In addition, there was increased mRNA expression of the cell adhesion marker P‐selectin in the thoracic aortic wall and the pro‐inflammatory marker IL‐1β in the left common carotid artery in preterm lambs, suggestive of postnatal vascular injury. Early postnatal differences in the function and structure of conduit arteries and evidence of vascular injury in moderately preterm offspring may place them at greater risk of cardiovascular impairment later in life. Abstract :